Mathematical modeling and experimental validation of the thermal performance of a novel design solar cooker. (1st September 2020) - Khallaf, A.M.; Tawfik, M.A.; El-Sebaii, A.A.; Sagade, Atul A.
Highlights: New design of solar cooker (QSC) is presented. Performance of the QSC is analyzed for low and intermediate temperature cooking activity. Impact of design change on performance of the QSC is assessed. Inter-cooker performance grading has been done. Abstract: The present work is aimed to report a new design of a solar cooker named as Quonset solar cooker (QSC). The cooker provided with transparent, lightweight and durable dome-shape polymeric glaze. The cooker enclosure is divided into dual cooking compartments with internal reflectors. The thermal performance of the cooker is assessed experimentally for low and intermediate temperature cooking activities. A mathematical model is presented to verify the thermal performance of the QSC through parametric analysis. The experimental results are compared to the model. Numerical results for validation purpose taking into consideration the thermal performance parameters (TPPs) such as; cooking power, cooker efficiency and cooker opto-thermal ratio (COR). The cooker has been graded by computing the two figures of merit F1 and F2 numerically. The results revealed that, the proposed design of the solar cooker can be used with water and glycerin as cooking fluids with efficiencies change from 6 to 35% and from 9 to 92%, respectively.